New Record of Anapistula (Gertsch 1941) (Araneae: Symphytognathidae) in Europe with the description of a new species - Pertegal, Cristian; Barranco, Pablo (Zootaxa, 2025)
A new species of the genus Anapistula Gertsch, 1941, A. delrosalae sp. nov., is described, marking the second record of the family Symphytognathidae in Europe. The new species has, to date, only been found in the Cueva de Nerja, Málaga (Spain). Based on the specimens collected, A. delrosalae sp. nov. appears to be present throughout the cave, from the Tourist Galleries to the New Galleries. Detection of the species is challenging due to its small size, which has likely caused it to go unnoticed until now. The new species is based on both somatic and genitalic morphological characters of females. The male is still unknown. The diagnostic characteristics that have been useful in distinguishing the new species from the already known Anapistula ataecina Cardoso & Scharff, 2009, native to the Frade cave system, Lisbon, Portugal, are discussed.